A Review on Pharmacovigilance Process In India - Mishra, Preti; Upadhyay, Pawan; Rawat, Ravi; dar, Tajamul Ashraf; Dev, Kapil; Chauhan, Nidhi (Asian Journal of Pharmaceutical Research and Development, 2020)
Peoples are using more potent drugs with various medical conditions. pharmacovigilance helps in safe and convenient use of pharmaceutical drugs. Voluntary recording of adverse drug reactions (ADRs) is a chief component of pharmacovigilance. Adverse drug reactions have become a dominant health related problems in developing countries like India. The main objective of pharmacovigilance is the assessment of benefit-risk profile of drug for better potency and safety in patients. In terms of volume India pharmaceutical industries is third largest in the world so India has a core of clinical research and drug design & development. This review article explains the need of pharmacovigilance in pharma companies, the growth of pharmacovigilance in different centuries and current status of pharmacovigilance in the country.